2021
DOI: 10.1002/gea.21841
|View full text |Cite
|
Sign up to set email alerts
|

Relative sea‐level changes along the Fethiye coast (SW Turkey) based on recent archaeological data

Abstract: We investigated three coastal archaeological sites along the coast of Fethiye (south‐western Turkey, eastern Mediterranean) to reveal relative sea‐level changes that have occurred since early Byzantine times. Focusing on this little known period, the most recent archaeological data are presented here, providing new data for the history of sea‐level changes. Current elevations of submerged archaeological remains relative to present sea level were measured, and relative sea‐level change was determined, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…An RSL rise of at least 2.8 m over the past 1400 years was suggested for Kekova (Özdaş & Kızıldağ, 2013). Recent studies on the Early Byzantine remains along the coast of Fethiye demonstrated that, over the last 1400 years, the sea level has risen by 2.2–3.1 ± 0.3 m on the eastern coast of Fethiye (Kızıldağ & Özdaş, 2021), while the western coasts portray a rise of 3.1–4.6 ± 0.3 m (Kızıldağ, 2019). This remarkable difference in the RSL changes between the regions confirms that local‐scale tectonic processes have an important effect on the submergence of coastal sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An RSL rise of at least 2.8 m over the past 1400 years was suggested for Kekova (Özdaş & Kızıldağ, 2013). Recent studies on the Early Byzantine remains along the coast of Fethiye demonstrated that, over the last 1400 years, the sea level has risen by 2.2–3.1 ± 0.3 m on the eastern coast of Fethiye (Kızıldağ & Özdaş, 2021), while the western coasts portray a rise of 3.1–4.6 ± 0.3 m (Kızıldağ, 2019). This remarkable difference in the RSL changes between the regions confirms that local‐scale tectonic processes have an important effect on the submergence of coastal sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, Antonioli et al (2007) and Auriemma and Solinas (2009) suggested a minimum functional elevation of 0.6 m above the MSL for harbor installations (e.g., piers, docks, and breakwaters), based on the observations collected at many submerged archeological sites along the coast of the Mediterranean. This assumption has been widely used in many sea level studies in recent years (Aucelli et al, 2016; Kızıldağ & Özdaş, 2021; Kolaiti & Mourtzas, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Underwater archaeological surveys carried out over the last 60 years demonstrate that the Turkish coasts are very rich in terms of underwater cultural heritage (Pulak, 1998;Ward & Ballard 2004;Bass, 2005;Royal, 2006;Brennan et al, 2012;Özdaş, 2010;Özdaş et al, 2012;Kızıldağ & Özdaş, 2021).…”
Section: Introductionmentioning
confidence: 99%